Association of diabetes and exposure to fine particulate matter (PM2.5) in the Southeastern United States - R. Burciaga Valdez; Mohammad Tabatabai; Mohammad Z. Al-Hamdan; Derek Wilus; Darryl B. Hood; Wansoo Im; Amruta Nori-Sarma; Aramandla Ramesh; Macarius M. Donneyong; Michael A. Langston; Charles P. Mouton; Paul D. Juárez (Elsevier, 2022)
Fine particulate matter (PM2.5) exposure can cause premature death and harmful chronic disease such as diabetes. The U.S. Environmental Protection Agency (EPA) sets annual PM2.5 standards to reduce these negative health effects. Currently, annual average exposure over 12 µg/m3 is considered unhealthy. This study tests whether individuals living in locations exposed to elevated ambient levels of PM2.5 concentrations were more likely to self-report diabetes. We examined the association of long-term exposure to PM2.5 and diabetes at enrollment (2002-2009) in a cohort of 44,610 individuals residing in 12 states, recruited into the Southern Community Cohort Study (SCCS). Annual average PM2.5 was estimated using remotely sensed satellite data integrated with ground monitoring data at participants' residence in urban and rural locations. We used multilevel mixed-effects logistic regression models to estimate the associations between self-reported diabetes and historical exposure to elevated ambient levels of PM2.5. We found a 10.1% increase in odds of reported diabetes with exposure to unhealthful levels of PM2.5 exposure (>12 µg/m3 at enrollment) compared to respondents living in areas with lower annual PM2.5 concentrations. Participants with medical histories of hypertension, hypercholesterolemia, and smoking had an overall 384% higher odds of reported diabetes than those without these clinical risk factors. Black participants were more likely to live in locations with higher ambient PM2.5 concentrations, report high levels of clinical risk factors, and had a 29.1% increase in odds of reported diabetes than Whites. In SCCS participants, exposures to high ambient levels of PM2.5 were associated with self-reported diabetes at enrollment. Reduction in PM2.5 standards for the U.S. are recommended.